Aplikasi Konsep Contemporer Pada Pusat Informasi Airsoft Gun - Antonius Daniswara; Stephanus P Honggowidjaja (Intra, 2014)
The design is made to increase community activities in sport, especially for the teenagers, this design also to introduces a new sport to community, the sport of airsoft gun. This design not only invites community to exercise but also to provide information of airsoft gun.                    This design uses the function space so that people can visit to get information clearly and a new place for an interentingly exercise, by displaying a collection of objects and their descriptions, and supported by an attractive interior atmosphere.